(untitled) (Revista de História Regional, 2007)
The aim of this article are the proposals of the scientist and doctor Aleixo de Vasconcellos, related with the school recreation. With this objective in mind, I analyzed a Vasconcellos work presented in 1924 to the Sociedade de Medicina e Cirurgia do Rio de Janeiro and published in two periodicals. The research is based on Michel Foucaults approach: we explore the vigilant looking of Vasconcellos about the schools, desiring to normalize, to impose hygienical procedures, in benefit of the defense of the species.